A comparative first-principles study of the lithiation, sodiation, and magnesiation of black phosphorus for Li-, Na-, and Mg-ion batteries. Issue 31 (18th July 2016) - Hembram, K. P. S. S.; Jung, Hyun; Yeo, Byung Chul; Pai, Sung Jin; Lee, Heon Ju; Lee, Kwang-Ryeol; Han, Sang Soo
Abstract : Lithiation, sodiation, and magnesiation of black phosphorus are clarified and compared using first-principles calculations. Abstract : Using first-principles calculations, we describe and compare atomistic lithiation, sodiation, and magnesiation processes in black phosphorous with a layered structure similar to graphite for Li-, Na-, and Mg-ion batteries because graphite is not considered to be an electrode material for Na- and Mg-ion batteries. The three processes are similar in that an intercalation mechanism occurs at low Li/Na/Mg concentrations, and then further insertion of Li/Na/Mg leads to a change from the intercalation mechanism to an alloying process. Li and Mg show a columnar intercalation mechanism and prefer to locate in different phosphorene layers, while Na shows a planar intercalation mechanism and preferentially localizes in the same layer. In addition, we compare the mechanical properties of black phosphorous during lithiation, sodiation, and magnesiation. Interestingly, lithiation and sodiation at high concentrations (Li2 P and Na2 P) lead to the softening of black phosphorous, whereas magnesiation shows a hardening phenomenon. In addition, the diffusion of Li/Na/Mg in black phosphorus during the intercalation process is an easy process along one-dimensional channels in black phosphorus with marginal energy barriers. The diffusion of Li has a lower energy barrier in black phosphorus than in graphite.